IMPACT OF FARMERS DEVELOPMENT UNION (FADU) LOAN SCHEME ON INCOME GENERATION OF FARM HOUSEHOLDS IN OYO STATE OF NIGERIA - DADA, A. D.; OKORUWA, V. O.; OGUNDELE , O. O.; ADEWUYI, S. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The impact of a Non-Governmental Organisation's (NGO)-based soft loan scheme on the income generation and expenditure patterns of farmers was investigated in Oyo State of Nigeria. The study was carried out in 13 Local Government Areas (LGAs) of the state. Data were collected from 151 farmers consisting of 81 NGO Credit Beneficiaries and 70 Non-Beneficiaries. Chow-test was used to determine the difference in income generation and expenditure patterns between beneficiaries and non-beneficiaries. Regression results showed income to be statistically significant for beneficiaries (P<0.05) and for non- beneficiaries (P<0.01). Credit was found to be negatively significant on farmers expenditures (P<0.1) for beneficiaries. The Chow-test value of F-Calculated was 0.123 and F-tabulated was 6.610. This showed that there was no significant difference in the expenditure patterns of both beneficiaries and non-beneficiaries. The study concluded that the size of credit granted to beneficiaries fall below the amount being demanded for by the farmers hence there was no impact of the NGO microcredit scheme on the income generation and expenditure patterns of farmers in the area investigated. There is therefore the need to expand the size of the credit/soft loans to the farmers by building linkages with the formal financial institutions.